THE ROLE OF DIGITAL IN LITERATURE AS SOCIAL MEDIUM IN TODAY'S TIME - Marulafau, Siamir (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2024)
This writing aims to describe how The Role of Digital in Literature as a social Medium in Today's time needs language as medium of communication obviously is inseparable from digital technology because of its authentic data used to prove. What have been discussed through digital like computer uses language and this may arise to the fact that using digital in case of writing literature is surely important to use. This writing presumably is tried to find out if digital like computer and others are useful in writing literary works like poems, short stories, essays, and novels regarding as a result of research conducted by the researcher. The method used in writing this research is descriptive method as a means of searching the fact related to the main topic being discussed based on the theory dealing with using digital technology in today's time